2020
DOI: 10.1016/j.displa.2019.101932
|View full text |Cite
|
Sign up to set email alerts
|

With flying colours: Pilot performance with colour-coded head-up flight symbology

Abstract: The manipulation of colour in display symbology design has long been recognised as a method to improve operator experience and performance. Recent developments in colour head-up display (HUD) and helmetmounted display (HMD) technology underline the necessity to understand the human factors considerations of symbology colour coding against conventional monochrome symbology formats. In this low-fidelity desktop human-in-the-loop experiment, the colour of flight symbology on an overlaid symbology set was coded as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…The primary finding from the study was that colour-coded feedback reduced the workload experienced by pilots, and that this perceived benefit was exclusive to flying conditions where pilots were under higher task load demands imposed by the presence of a secondary task. The absence of a reported workload benefit under low task load conditions is in line with the findings from our previous study [23]. In addition, the current findings clarifies the nature in which workload was likely reduced in Dudfield's 1991 study [22], where the specificity of the colour-coded related workload benefit was not reported.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The primary finding from the study was that colour-coded feedback reduced the workload experienced by pilots, and that this perceived benefit was exclusive to flying conditions where pilots were under higher task load demands imposed by the presence of a secondary task. The absence of a reported workload benefit under low task load conditions is in line with the findings from our previous study [23]. In addition, the current findings clarifies the nature in which workload was likely reduced in Dudfield's 1991 study [22], where the specificity of the colour-coded related workload benefit was not reported.…”
Section: Discussionsupporting
confidence: 90%
“…Dudfield [22] found that colour-coded error feedback provided on HUD flight symbology did not support pilot flying accuracy during straight and level flight, but did benefit subjective workload. Findings from our own recent study [23] demonstrated that a similar colour-coded head up symbology set granted minor and major flying accuracy enhancements to professional airline pilots and novices, respectively. It is likely that the performance benefits found in our study arose from the more varied range of manoeuvres, such as climbing turns, that required pilots to attend to both dynamic and static flight parameters.…”
Section: Introductionmentioning
confidence: 87%
“…For example, one participant remarked that the haptics acted as an effective "attention getter" during long straights to notify pilots of upcoming turns when arousal might have declined. Implementation of redundant cues from basic and applied research have reported similar effects [29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Performance feedback could take different forms. In some tasks, some display element turned green or red, indicating good or poor performance, respectively (Blundell et al, 2020a). In other tasks, a virtual agent gave verbal performance feedback (e.g., “Wow, you are really good at this”; Wang, Buchweitz, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%